Contribution of Fishermen’s Wives (Patorani) Income to Household Income Bontomarannu Village, Galesong Selatan District, Takalar Regency - Eni Jumrieni; Saleh Molla; Nadir (Tarjih : Agribusiness Development Journal, 2026)
This study analyzes the economic role and income contribution of fishermen’s wives (patorani) to total household income in Bontomarannu Village, Galesong Selatan District, Takalar Regency. A survey method with purposive sampling was employed, involving 15 respondents. Primary data were collected through interviews and field observations, while secondary data were obtained from statistical reports and relevant literature. Data were analyzed using descriptive quantitative and qualitative approaches. The results show that fishermen’s wives perform dual roles by managing domestic responsibilities while participating in productive activities such as fish processing, small-scale trading, and agricultural labor. The average monthly income earned by fishermen’s wives was IDR 1,239,780, while the average total household income reached IDR 4,012,266. The wives’ income contribution was 30.89%, which is categorized as low (<35%). Despite the relatively modest percentage, women’s economic participation plays a strategic role in stabilizing household income and reducing vulnerability to seasonal fluctuations in coastal communities.